Nature Inspired MXene-Decorated 3D Honeycomb-Fabric Architectures Toward Efficient Water Desalination and Salt Harvesting - Lei, Zhiwei; Sun, Xuantong; Zhu, Shifeng; Dong, Kai; Liu, Xuqing; Wang, Lili; Zhang, Xiansheng; Qu, Lijun; Zhang, Xueji (Nano-Micro Letters, 2021)
Solar steam generation technology has emerged as a promising approach for seawater desalination, wastewater purification, etc. However, simultaneously achieving superior light absorption, thermal management, and salt harvesting in an evaporator remains challenging. Here, inspired by nature, a 3D honeycomb-like fabric decorated with hydrophilic Ti3C2Tx (MXene) is innovatively designed and successfully woven as solar evaporator. The honeycomb structure with periodically concave arrays creates the maximum level of light-trapping by multiple scattering and omnidirectional light absorption, synergistically cooperating with light absorbance of MXene. The minimum thermal loss is available by constructing the localized photothermal generation, contributed by a thermal-insulating barrier connected with 1D water path, and the concave structure of efficiently recycling convective and radiative heat loss. The evaporator demonstrates high solar efficiency of up to 93.5% and evaporation rate of 1.62 kg m−2 h−1 under one sun irradiation. Moreover, assisted by a 1D water path in the center, the salt solution transporting in the evaporator generates a radial concentration gradient from the center to the edge so that the salt is crystallized at the edge even in 21% brine, enabling the complete separation of water/solute and efficient salt harvesting. This research provides a large-scale manufacturing route of high-performance solar steam generator. Highlights: 1 The 3D honeycomb-like fabric decorated with MXene is woven as solar evaporator. 2 The honeycomb structure enables light-trapping and recycling of convective and radiative heat. 3 The 3D honeycomb-fabric evaporator possesses high solar efficiency up to 93.5% under 1 sun irradiation and excellent salt harvesting ability.